Probabilistic Approach for Virtual Screening Based on Multiple Pharmacophores - Madzhidov, Timur I; Rakhimbekova, Assima; Kutlushuna, Alina; Polishchuk, Pavel (Molecules (Basel, Switzerland), 2020)
Pharmacophore modeling is usually considered as a special type of virtual screening without probabilistic nature. Correspondence of at least one conformation of a molecule to pharmacophore is considered as evidence of its bioactivity. We show that pharmacophores can be treated as one-class machine learning models, and the probability the reflecting model's confidence can be assigned to a pharmacophore on the basis of their precision of active compounds identification on a calibration set. Two schemes (Max and Mean) of probability calculation for consensus prediction based on individual pharmacophore models were proposed. Both approaches to some extent correspond to commonly used consensus approaches like the common hit approach or the one based on a logical OR operation uniting hit lists of individual models. Unlike some known approaches, the proposed ones can rank compounds retrieved by multiple models. These approaches were benchmarked on multiple ChEMBL datasets used for ligand-based pharmacophore modeling and externally validated on corresponding DUD-E datasets. The influence of complexity of pharmacophores and their performance on a calibration set on results of virtual screening was analyzed. It was shown that Max and Mean approaches have superior early enrichment to the commonly used approaches. Thus, a well-performing, easy-to-implement, and probabilistic alternative to existing approaches for pharmacophore-based virtual screening was proposed.
Keywords: molekulární konformace; ligand-based virtual screening; Ligands; Models, Molecular; Molecular Conformation; Drug Evaluation, Preclinical; léčivé přípravky; Humans; preklinické hodnocení léčiv; ligandy; Pharmaceutical Preparations; Protein Binding; chemické modely; Computer Simulation; Machine Learning; machine learning; lidé; zvířata; molekulární modely; počítačová simulace; Models, Chemical; strojové učení; virtual screening; pharmacophores; vazba proteinů; Animals